STATUS TAKSONOMI PSIDIUM CUJAVILLUS BURM.F. - Yachinta Azhari Br. Marpaung; Alex Hartana (Floribunda, 2014)
The taxonomic position of Psidium cujavillus Burm.f. in relation to P. guajava L. has not been widely agreed upon, so that this research was conducted to clarify it based on morphological characteristics, germination, anatomy, and chromosomes. Observations on the living material of P. cujavillus and P. guajava showed that there were basic similarities in the structure and forms except in segment distance and size of leaves, fruit diameter and seed weight. Both taxa have the same germination processes, and their seedlings morphology are also not much different except in size. Anatomically there were also no significant differences between P. cujavillus and P. guajava. Chromosome size of P. cujavillus and P. guajava do not exceed 2 μm, both has the number of 2n=22. Overall observation showed that there was no significant difference to indicated P. cujavillus as distinct species from P. guajava. Based on this, it is suggested that P. cujavillus should be classified as a infraspecies variation in P. guajava.